TASHMIM AL MANHAJ WA KITAB TA’LIM AL LUGHAH AL ARABIYAH LIL MARHALAH AL JAMI’IYAH FI DHAUI MA’AYIIR AL ITHOR AL WATHANY AL INDUNISY LIL MUAHHILAT (KKNI) - nor, fatwiyah (Ijaz Arabi Journal of Arabic Learning, 2018)
The results of this study are: 1) the educational curriculum in the KKNI which contains: (a) educational objectives consisting of cognitive, managerial, behavioral and behavioral aspects, (b) material for reading skills, and (c) composition; 2) Textbooks contain: (a) objectives and achievement indicators, 1) Arabic language curriculum based on IQF which contains: (a) educational objectives consisting of cognitive, managerial and behavioral aspects, (b) themes that are in line with the Ahwal Syahshiyah department, (c) teaching methods that are used, (d) basic rules, (e) evaluation of reading skills, (f) vocabulary. 3) This book is good to use because it affects the improvement of academic achievement.The results of the study show that the education process considers students as the center of explorative, applied and collaborative teaching and learning activities.